DEVELOPING STUDENTS’ WRITING AND DIGITAL LITERACY USING WEBLOG AT TRIDINANTI UNIVERSITY OF PALEMBANG - Heru Setiawan; Farnia Sari (Sriwijaya University Learning and Education International Conference, 2018)
This research was aimed at investigating the development of students’ writing and digital literacy through weblog. The sample of the study was 20 students of the fourth semester English study program of Tridinanti University Palembang. The researchers used purposive sampling as the way of choosing the sample because the sample is taught by the researchers in writing class. The researchers applied quasi-experimental design in term of pretest-posttestnon equivalent group design. Moreover, there are three types of data collection used by the researchers; they are test, questionnaire and observation. After the study, it was found out that the results of posttest between experiment and control group show significant difference with t value of posttest was 11.739, sig 0.000 while t value of gain score was 7.671, sig 0.000. Accordingly, all aspects of writing both posttest and gain score show significant differences. Furthermore, it was also found that the developments of digital literacy components from the highest to the lowest are as follows: 1) information sources (36%), 2) digital competencies (23%), 3) attitude and perspective (24%), and 4) basic ICT skill (17%). As the results, this reserach reveals that weblog is effective to develop students’ writing and digital literacy. In addition, students showed positive views because using blog was very interesting and it provided more cooperation between lecturer and students